2012
DOI: 10.1186/1471-2482-12-s1-s8
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes of colon laparoscopic resection in the elderly patients compared with the younger

Abstract: BackgroundThe aim of this study was to define any benefits in terms of early outcome for laparoscopic colectomy in patients over 75 years old (OP) compared with the outcomes of a younger populations (YP).MethodsForty elderly patients undergoing laparoscopic colectomy for colorectal cancer between 2007-2011 were studied, the patients are divided for gender, age, year of surgery, site of cancer, and comorbidity on admission and compared with 40 younger patients.Results and discussionMean (standard deviation) age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
3
20
0
3
Order By: Relevance
“…Previous studies have demonstrated short-term advantages of laparoscopic colorectal resection in the elderly population, including a reduction in the length of hospital stay, intraoperative blood loss, time to return of normal bowel function, incidence of postoperative cardiac complications, and wound infections. [4][5][6][7][8][9][10] Despite using laparoscopy and enhanced recovery pathways (eRPs), some elderly patients are not ready for early discharge. frailty may be a major factor.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated short-term advantages of laparoscopic colorectal resection in the elderly population, including a reduction in the length of hospital stay, intraoperative blood loss, time to return of normal bowel function, incidence of postoperative cardiac complications, and wound infections. [4][5][6][7][8][9][10] Despite using laparoscopy and enhanced recovery pathways (eRPs), some elderly patients are not ready for early discharge. frailty may be a major factor.…”
mentioning
confidence: 99%
“…This procedure should be used selectively in older patients with limited cardiopulmonary reserves. Several studies report that, with advancement of anesthetic and surgical techniques, laparoscopic colorectal Bottino et al 8 compared postoperative outcomes in two groups divided according to the age of 75 years. Conversion rate to open surgery was the same between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 With advancement of laparoscopic techniques, several studies show that laparoscopic colorectal surgery is a safe and feasible procedure, even in elderly patients. 8,9 However, the safety of laparoscopic surgery in elderly patients after preoperative chemoradiation is unknown. The aim of this study was to evaluate the safety of laparoscopic surgery for rectal cancer after preoperative chemoradiation in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, mainly retrospective series, suggest that both surgical and medical treatments in this population are as safe and effective as in the younger population [ [42], [43], [44]], but data on an integrated conversion strategy are lacking. The current evidence supports treatment for fit elderly patients, who can achieve similar outcomes to that of younger patients [45].…”
Section: Individualized Approachmentioning
confidence: 99%